Method of controlling the cyclotron motion of electron beams with a nonadiabatic magnetic field - Pikin, Alexander; Pahl, Hannes; Wenander, Fredrik (Physical review accelerators and beams, 2020)
This paper describes a method for reducing the energy of the cyclotron motion for charged particles in coherent beams using a nonadiabatic magnetic field. For the purpose of reducing the cyclotron motion, a local magnetic field reduction of the main guiding field should be situated in the region of the descending phase of the beam oscillation. The required local magnetic field depression can be produced with a soft iron ring or with a magnet coil. The nonadiabatic element can be positioned on the descending part of any period of the beam oscillation where the beam still remains sufficiently coherent. The effect of reducing the cyclotron motion with such nonadiabatic magnetic field is independent of the electric field of the cathode-anode gap and seems to be a universal method for the cyclotron motion control in coherent beams. Therefore, it can be used for reducing the cyclotron motion of electron beams produced with different kinds of guns with different perveances and sizes. For instance, the method is capable of creating ripple-free, laminar beams even for magneto-immersed guns positioned in a magnetic field of only a few hundred Gs and with a cathode emission current density exceeding 30 A/cm2. It can also be applied for guns producing tubular beams, as demonstrated by our simulations. The results of computer simulations are presented, which demonstrate the capability of effective cyclotron motion control with nonadiabatic magnetic field.
Gesehen am 24.11.2020